The Effect of Organization Culture Moderation and Big Five Personality on the Influence of Working Culture Towards the Performance of Jambi Provincial Government Civil Servants - Desmaryani, Susi (Jurnal Bina Praja, 2018)
Services provided by civil servants of Jambi Provincial Government is still not as expected by the community. Performance of civil servants is still not yet directed to service oriented. For that reason, work culture must be created that leads to performance achievement supported by the organizational culture and the personality of civil servants themselves in providing services. This study aims to determine: (1) Illustration of Organizational Culture, Big Five Personality as a moderation variable and work culture and performance as a moderated variable. (2) Effect of moderation of organizational culture on the interaction of work culture and civil servant’s performance in Jambi Provincial Government, (3) Big Five Personality Moderation effect on the interaction of work culture and civil servant’s performance in Jambi Province Government. The types of research are descriptive and verificative. Multistage random sampling technique is sampling in two stages; first, identifying SKPD, Bureau, and Agency, and second, determining the number of respondents from each SKPD, Bureau, and Agency. Data analysis is descriptive and inferential analysis is using path analysis. The results describe the organizational culture descriptively, Big Five personality as moderate variables are in a good category, work culture and performance as moderated variables are in a good category. Even so, organizational culture as a moderating variable is weakening the influence of work culture on performance if compared to direct influence between organizational culture on work and work culture on performance. On the other hand, the moderating variables are able to strengthen the influence of work culture on the performance of civil servants in the Jambi Provincial Government, compared to the Big Five Personality’s direct contribution to performance and work culture on performance. Therefore, every Department, Agency, Bureau, and UPTD reassess whether the culture applied is in accordance with the character, personality, and demands of the external environment, so that organizational culture is able to strengthen the influence of work culture on performance.